2011
DOI: 10.1088/0957-4484/22/27/275704
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structures of an epitaxial graphene monolayer on SiC(0001) after gold intercalation: a first-principles study

Abstract: The atomic and electronic structures of an Au-intercalated graphene monolayer on the SiC(0001) surface were investigated using first-principles calculations. The unique Dirac cone of graphene near the K point reappeared as the monolayer was intercalated by Au atoms. Coherent interfaces were used to study the mismatch and the strain at the boundaries. Our calculations showed that the strain at the graphene/Au and Au/SiC(0001) interfaces also played a key role in the electronic structures. Furthermore, we found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
28
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 26 publications
2
28
0
Order By: Relevance
“…Only graphene on Ir(111) displays a lower level of charge transfer; however, in that case the electronic structure of graphene is complicated by interactions with the Ir bands close to the Fermi level. As these interactions are absent in graphene on Au(111), this system is well suited for investigations of quasi-free-standing graphene, an attribute that is being investigated in transferred and Au-intercalated graphene [25,[30][31][32]. Table 1.…”
mentioning
confidence: 99%
“…Only graphene on Ir(111) displays a lower level of charge transfer; however, in that case the electronic structure of graphene is complicated by interactions with the Ir bands close to the Fermi level. As these interactions are absent in graphene on Au(111), this system is well suited for investigations of quasi-free-standing graphene, an attribute that is being investigated in transferred and Au-intercalated graphene [25,[30][31][32]. Table 1.…”
mentioning
confidence: 99%
“…The study by Gierz et al 17 demonstrated that the strongly interacting first graphitic layer was decoupled from the SiC(0001) substrate via gold intercalation. The shifts of Dirac points due to gold intercalation were then theoretically studied by Chuang et al 19 The choice of elements used for intercalation depends on the atomic radius such that the atoms can fit into the supercell. On the other hand, it depends on their interatomic bond strength meaning the intercalated atoms will not break the sp 2 hybridization of the graphene.…”
mentioning
confidence: 99%
“…The calculations were carried out within the generalized gradient approximation to the densityfunctional theory (DFT) 26,27 using projector augmentedwave (PAW) pseudopotential method, 28 as implemented in the Vienna Ab-initio Simulation Package (VASP). 29 As in previous studies, 4,5,11,19 a ffiffi ffi 3 p  ffiffi ffi 3 p R30 unit cell of SiC(0001) is used to match the 2  2 unit cell of graphene. The same computational settings are used as in Ref.…”
mentioning
confidence: 99%
“…The study by Gierz et al [21] claimed that the strongly interacting first carbon layer was decoupled from the SiC(0 0 0 1) substrate via gold intercalation. The shift of Dirac points due to gold intercalation was then theoretically studied by Chuang et al [22]. A similar study performed by Premlal et al [23], using scanning tunneling microscopy and spectroscopy (STM/ STS), concluded that the intercalated gold cluster displays a new surface reconstruction and induces a possible hole-doping effect.…”
Section: Introductionmentioning
confidence: 87%
“…Nevertheless, we cannot exclude that a small shift of the Dirac point (below 20 meV) has occurred. Moreover, Au deposition on SiC(0 0 0 1) results in p-or n-doping, depending either on the number of graphene layers, the strain at the Au/graphene or SiC/ graphene interfaces [22], or the gold coverage [21]. In our case, we average the electronic information over the region that is slightly larger than that defined by the illumination, which includes both single and bilayer graphene.…”
Section: Au Intercalation In Epitaxial Graphene On Sic(0 0 0 1)mentioning
confidence: 99%